Italian minister to the court of Haile Selassi of Ethiopia. From: Keesings Wereldgebeuren in Beeld, p.445 (1935)
Italian minister to the court of Haile Selassi of Ethiopia. From: Keesings Wereldgebeuren in Beeld, p.445.